Post-Crisis Recovery : When Does Increased Fiscal Discipline Work? - Mitra, Pritha (IMF Working Papers; Working Paper ;, 2006)
Emerging market financial crises during the late 1990s were marked by sudden withdrawals of funds by foreign creditors, resulting in production declines. The IMF favored positive signals to potential foreign creditors and initially recommended disciplined fiscal policy during the height of crisis, countering standard Keynesian recommendations of expansionary fiscal stimulus. This paper formulates an open-economy general equilibrium model for resolving this policy conundrum and analyzing the impact of disciplined fiscal policy on post-crisis recovery. The model demonstrates via simulations that disciplined fiscal policy will improve (worsen) post-crisis recovery in the presence (absence) of appropriately defined production flexibility.